A review on synthesis and applications of nano metal Oxide/porous carbon composite. (2022) - Bijesh, Priya; Selvaraj, V.; Andal, V.
Abstract: The growing demand on energy storage devices and environmental issues has enhanced the curiosity for metal oxide/porous carbon composite owing to its intriguing properties. Nano metal oxides undergo aggregation at high temperature. To overcome the issues, the studies on nano metal oxides incorporated into the porous carbon matrix are carried out. This review article discuss about the various synthetic strategies of metal oxide/porous carbon composite and their applications towards the environmental, energy devices, catalyst, sensors, etc. In particular the porosity of the carbon with respect to the physiochemical properties of metal oxide/porous carbon composite are discussed and reported. The future trends and development on the nano metal oxide/porous carbon composite and its applications in various fields are discussed.